First isolation in Argentina of a highly virulent Shiga toxin-producing Escherichia coli O145:NM from a domestic cat - María Valeria Rumi; Kinue Irino; Natalia Deza; Miguel J Huguet; Adriana B Bentancor (Journal of Infection in Developing Countries)
Introduction: Hemolytic uremic syndrome (HUS) is distributed worldwide. In Argentina, more than 450 cases of HUS, mostly sporadic, are reported annually. The main serotype isolated is O157:H7, and among non-O157 STEC, O145:NM is the most frequent strain. We studied the relationship of companion animals living in contact with a child with sporadic HUS, as carriers of Shiga toxin-producing Escherichia coli (STEC) strains.